SAT0076 Beneficial Effects of Atorvastatin Treatment in Smoking Patients with Rheumatoid Arthritis and Hypercholesterolaemia. (23rd January 2014) - Rupinski, R.; Lewandowski, Z.; Walewska, E.; Gluszko, P.
Abstract : Background: Cigarette smoking significantly increases the risk of cardiovascular diseases (CVD) and predisposes to rheumatoid arthritis (RA) development. Objectives: Investigate the impact of smoking on serum pro-atherogenic chemokines (CX3CL1 – fractalkine, CCL2 – monocyte chemotactic protein-1, CCL5 – RANTES) and endothelial derivatives (ICAM-1 – intercellular adhesion molecule-1, VEGF – vascular endothelial growth factor) levels in RA patients with hypercholesterolaemia treated with atorvastatin (ATS). Methods: The study included 36, mainly female (91.7%), RA patients (age – 60.1±7.6 years, anti-CCP positive – 75.0%, total cholesterol – 259±26 mg/dl). All patients received a 16 week ATS treatment, 10 mg daily, according to ATP III guidelines. The Systematic Coronary Risk Evaluation (SCORE) was assessed and serum CX3CL1, CCL2, CCL5, ICAM-1 and VEGF levels were measured using ELISA (R&D Systems) before and after the ATS treatment. Cigarette smoking was determined as being an ever-smoker (63.9%) or a never smoker (non-smoker). A statistical analysis was performed using Mann-Whitney and Wilcoxon tests (Statistica v. 10). Results: No statistically significant differences were found between smokers and non-smokers at the beginning of the observations, except for SCORE (7.13 vs. 3.92, p=0.031) and the disease duration (6.4 vs. 15.9 years, p=0.002). SCORE values, total cholesterol and ICAM-1 serum concentrations decreased during the study in both groups; in smokers: 7.13 vs. 4.44 (p=0.001), 258 vs. 197 mg/dl (p<0.001), 130 vs. 113 pg/ml (p=0.005), respectively, and in non-smokers: 3.29 vs. 3.00 (p=0.069), 261 vs. 213 mg/dl (p=0.012), 132 vs. 108 pg/ml (p=0.018), respectively. After the ATS treatment, CX3CL1 and CCL5 levels dropped significantly only in ever-smoking patients: 1779 vs. 1446 pg/ml (p=0.031) and 1348 vs. 1020 pg/ml (p=0.001), respectively. The ATS treatment had no effect on serum CCL2 and VEGF throughout the observation period. Conclusions: By lowering serum cholesterol, the atorvastatin treatment reduces the risk of CVD (SCORE) in smoking and non-smoking RA patients. Ever-smoking RA patients may benefit additionally from a routine statin use, as atorvastatin simultaneously normalizes serum levels of some pro-atherogenic chemokines and endothelial derivatives. Disclosure of Interest: None Declared